Bitskrieg : the new challenge of cyberwarfare - Arquilla, John author. (Cambridge ; Medford : Polity, 2021)
"Pioneer of the concept of "netwar" explains why Bitskrieg is here to stay"-- Includes bibliographical references and index. "Cool War" Rising -- Pathways to Peril -- The Next Face of Battle -- (Arms) Ctrl+Alt+Esc -- Through a Screen Darkly. "Pioneer of the concept of "netwar" explains why Bitskrieg is here to stay"--